2022
DOI: 10.1038/s41597-022-01723-6
|View full text |Cite
|
Sign up to set email alerts
|

GABB: A global dataset of alpine breeding birds and their ecological traits

Abstract: Alpine ecosystems represent varied climates and vegetation structures globally, with the potential to support rich and functionally diverse avian communities. High mountain habitats and species are under significant threat from climate change and other anthropogenic factors. Yet, no global database of alpine birds exists, with most mountain systems lacking basic information on species breeding in alpine habitats, their status and trends, or potential cryptic diversity (i.e., sub-species distributions). To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Using a global dataset of alpine breeding birds (de Zwaan et al, 2022a(de Zwaan et al, , 2022b, we found that the proportion of passerines nesting in rock cavities was greater in the southern Andes (this study site; 54%; 13 of 24 species) than in other major temperate alpine communities globally (excluding species that breed above treeline rarely or incidentally). In the southern ranges of Europe (e.g., Alps, Pyrenees, Carpathians), 39% (12 of 31) of alpine breeding passerines nest in rock cavities, compared with 24% (9 of 38) in the coastal and Rocky Mountains of North America, and 22% (26 of 117) on the Qinghai-Tibetan Plateau.…”
Section: Rock Cavitymentioning
confidence: 88%
See 3 more Smart Citations
“…Using a global dataset of alpine breeding birds (de Zwaan et al, 2022a(de Zwaan et al, , 2022b, we found that the proportion of passerines nesting in rock cavities was greater in the southern Andes (this study site; 54%; 13 of 24 species) than in other major temperate alpine communities globally (excluding species that breed above treeline rarely or incidentally). In the southern ranges of Europe (e.g., Alps, Pyrenees, Carpathians), 39% (12 of 31) of alpine breeding passerines nest in rock cavities, compared with 24% (9 of 38) in the coastal and Rocky Mountains of North America, and 22% (26 of 117) on the Qinghai-Tibetan Plateau.…”
Section: Rock Cavitymentioning
confidence: 88%
“…We also provide natural history notes on breeding phenology, parental care, and resource competition to provide a baseline for future studies to build on within these data-deficient communities (Table 1). Finally, we compare the predominance of rock cavity-nesting species above treeline in the temperate Andes with other temperate alpine songbird communities using a global alpine breeding bird dataset (de Zwaan et al, 2022a(de Zwaan et al, , 2022b and generate a hypothesis framework for investigating variation in nest traits among alpine communities.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Rockjumpers fulfil multiple criteria necessary to be considered an indicator species for the adverse effects of climate change (see Carignan & Villard 2002). For instance, they occur only on continental sky islands (McCormack et al 2009), are probably climate relicts (Woolbright et al 2014), and they show a high degree of habitat specialization and restriction, in common with many mountain endemics (Scridel et al 2018, de Zwaan et al 2022. Additionally, they appear unable to shift their range if current habitat becomes thermally unsuitable (Kupfer et al 2005), and their Mountain Fynbos habitat is at high risk of size reduction from climate change (Simmons et al 2004).…”
Section: Study Speciesmentioning
confidence: 99%